Descended marginal sinus of the placenta. Issue 4 (18th March 2019) - Ryo, Eiji; Namai, Shigenari; Nakagawa, Ippei; Kanda, Ranka; Yatsuki, Keita; Ayabe, Takuya
Key Clinical Message: This is the first reported case of descent of the placental marginal sinus through the cervix to the external os. We think marginal sinus rupture does exist. The definition of placental edge should be the parenchyma in diagnosis of low‐lying placentation. Clinically, however, the low‐lying marginal sinus should be treated similar to low‐lying placentation. Abstract : This is the first reported case of descent of the placental marginal sinus through the cervix to the external os. We think marginal sinus rupture does exist. The definition of placental edge should be the parenchyma in diagnosis of low‐lying placentation. Clinically, however, the low‐lying marginal sinus should be treated similar to low‐lying placentation.